Research on solder joint stress damage evaluation method based on discrete SSI model. Issue 3 (January 2021) - Rong, K Y; Zhang, S J; Li, Y R Y; Wan, B
Abstract: Based on the discrete SSI(Stress-strength-interference) model, this paper establishes a stress damage evaluation method for the through-hole insertion process. First, based on the Monte Carlo sampling method, the mean value of solder joint stress was clarified, and a stress-strength interference model for through-hole insertion was established. Secondly, after calculating the shape of the solder joints of the through-holes, the simulated load input curve is determined and the stress simulation is performed to obtain the stress and strain simulation results. The stress and strain of the PCB board are measured through experiments. Finally, a random stress model of solder joints was established by Monte Carlo sampling, and a constant strength model of through-hole solder joints was established in combination with material strength. According to the stress strength interference model, the failure probability of process stress damage was calculated, and the stress damage evaluation of solder joints in through-hole insertion process was realized.